The Role of Emerging Technologies in Enhancing Accounting Practices - Shafeay, Karrar Mohammed AL (Research Parks Publishers, 2024)
This study explores the potential of emerging technologies, specifically blockchain and artificial intelligence (AI), to enhance accounting practices within Iraqi economic units. With a sample of 150 responses from accountants and financial managers, the research investigates the correlation between the application of these technologies and improvements in accounting processes. Findings reveal a significant association between the use of AI systems and blockchain technology in enhancing accounting practices. The study underscores the importance of leveraging emerging technologies to streamline data processing, enhance accuracy, reduce costs, and facilitate informed decision-making in accounting. These results highlight the transformative impact of technological advancements on accounting methods in the context of the Iraqi economy, suggesting avenues for further research and practical implications for stakeholders in the field.